Reaction‐Kinetics‐Tuned Synthesis of Platinum Nanorods and Nanodendrites with Enhanced Electrocatalytic Performance for Oxygen Reduction. Issue 12 (13th June 2016) - Xiong, Xiaoli; Liao, Yuxiang; Du, Cheng; Luo, Wei; Chen, Shengli
Abstract: We report a facile strategy to tune the growth behavior and surface structures of Pt nanocrystallites by varying the concentration of oleylamine (OAm) in mixed solutions of OAm and octadecene (ODE); the resulting Pt nanorods (NRs) and nanodendrites (NDs) show superior electrocatalytic performance for the oxygen reduction reaction (ORR). Long wormlike NRs with uniformly small diameters and NDs branched with NRs were obtained at low and medium concentrations of OAm, respectively. Time‐dependent morphology measurements showed that small Pt nanoparticles (NPs) were initially formed, which evolved into NRs or NDs depending on the reaction kinetics for Pt atom formation. Benefiting from the selective exposure of the ORR‐active (111) facet, the wormlike Pt NRs exhibited significantly higher ORR activity and electrochemical stability than state‐of‐the‐art Pt NP catalysts, which are enclosed with both the (111) and (100) facets. The ORR activity and stability of these catalysts were further enhanced by forming Pt NDs, probably as a result of the fact that the NR‐interconnected architectures produce more‐active high‐index facets in the junction areas. Abstract : It's a small world : Pt nanorods (Pt NRs) and nanodendrites (Pt NDs) are made by simple facial synthesis; small Pt nanoparticles (NPs) evolve into NRs or NDs depending on the reaction kinetics by tuning the volume ratio of oleylamine/octadecene. Furthermore, the electrocatalytic performance for the oxygen reduction reaction follows the order Pt/C<Pt NRs/C<Pt NDs/C ( see picture, MA=mass activity, SA=specific activity).